Innowacyjność regionów w Polsce - Węgrzyn, Grażyna (Region innovation in Poland, 2005)
The B&R and innovation activities are ment to be the factors responsible for both the region and the whole economy competitivness. In this study the author has identified the differences of the innovation level between provinces in Poland. As the analysis shows both the B&R and scientific potentials are concentrated in three provinces: mazowieckie, małopolskie i śląskie. These three provinces toegether engage 63% of nation’s investment outlay directed to B&R activity, while the other 13 provinces engage only 37%.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 63-71